Erratum to Comparison of I-Gel and classic Laryngeal Mask Airway in paediatric population: a parallel group study - Sharma, Apurb (Journal of Society of Anesthesiologists of Nepal, 2017)
This erratum is issued to a recently published original article titled "Comparison of I-Gel and classic Laryngeal Mask Airway in paediatric population: a parallel group study" in 2016, Volume 3, Number 2.